The Hungarian Start-up Ecosystem: A Comprehensive Overview - Radácsi, László (Improving Entrepreneurial Journey, 2025)
This chapter explores the Hungarian start-up ecosystem, a critical component for fostering economic growth, innovation, and societal change. It begins with a historical overview, setting the stage for an analysis of Hungary's entrepreneurial journey and current start-up landscape, highlighted by key statistics. The chapter examines the societal environment, including values and perceptions surrounding entrepreneurship, and the state and governmental measures impacting the start-up sector. A detailed exploration of the funding landscape identifies key sources of capital and investment trends. Additionally, the chapter addresses entrepreneurship education, a significant barrier to the ecosystem's development. Through case studies of notable Hungarian start-up programs, the chapter showcases contributions to the ecosystem. The discussion is framed using established ecosystem models, leading to conclusions about the primary challenges facing the Hungarian start-up ecosystem, including access to funding, education, cultural attitudes, regulatory hurdles, and talent retention. Recommendations are provided to overcome these barriers, ensuring a sustainable and dynamic entrepreneurial environment in Hungary.